KAJIAN PELAYANAN BUS ANTAR KOTA DALAM PROPINSI UNTUK MENGAKOMODASI PERMINTAAN PERJALANAN PENGGUNA BUSDI TERMINAL TIRTONADI SURAKARTA - Vera Novitasari; Kuswanto Nurhadi; Isti Andini (ARSITEKTURA, 2016)
Abstract:Surakarta city has a transport network nodes or terminals, Terminal Tirtonadi. The existence of a passenger bus fleet AKAP and AKDP continued to decline from 2010 to 2013 while in one day, the bus terminal Tirtonadi approximately 6000 people conducting the transportation of various routes stretch. This is due to AKAP bus services and AKDP less well from the bus waiting time is too long and less regular bus arrival. This study is expected performance of the bus at Terminal Tirtonadi accommodate travel demand bus users can be known. Approach to research conducted using quantitative descriptive approach. Data collection techniques done several ways including field survey and survey institution. The sampling technique used in conducting this research is quota sampling, sampling amount taken is 360 pieces. In the analysis performed it is known among other things, on weekdays for operational performance bus at the bus terminal bus performance Tirtonadi gained some less appropriate among other cost, bus waiting time and comfort level. As for the bus performance is the perception by the bus, it was concluded that all buses operating performance is moderate, not too good or not too bad. For the holidays, obtained operational performance bus at Terminal Tirtonadi there are some who do not fit between the other rates, waiting times, and the comfort level. As for the bus performance is the perception by the bus, it was concluded that all buses operating performance is moderate, not too good or not too bad. Keyworsd:AKDP Buses, Bus operating performance, Terminal Tirtonadi